1995
DOI: 10.1017/s0022336000026998
|View full text |Cite
|
Sign up to set email alerts
|

Chronostratigraphy and “Land-Mammal Ages” in the Cenozoic of southern South America: principles, practices, and the “Uquian” problem

Abstract: The concept of “land-mammal age” as developed in South America is examined. The “Uquian Land-mammal age” is used as a study case. “Land-mammal age” parataxonomy is here considered methodologically but not conceptually different from chronostratigraphic taxonomy. “Land-mammal ages” in South America are based on stages. However, we consider that accurate biostratigraphic studies must be done in South America for establishing the biostratigraphy and precise boundary stratotypes of most stages-ages. The Uquia outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
33

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 34 publications
3
115
0
33
Order By: Relevance
“…Sobre la unidad precedente, identifican un nivel litológicamente similar a la Formación La Postrera (sensu Fidalgo et al, 1973a), al que dividen en dos subniveles. El subnivel inferior (Lf M) es el portador de la asociación mamaliana sobre la que establecen la Fauna Local «Centinela del Mar», provisoriamente referida a una nueva Unidad Mamífero denominada «Centinelense», asignable al Pleistoceno Superior y anterior a la Unidad Mamí-fero Lujanense (para una definición de estas unidades bioestratigráficas véase Tonni et al, 1985Tonni et al, , 1987; para una crítica a las mismas véase Cione & Tonni, 1995). El subnivel superior (Lf N) es referido a la Unidad Mamífero Lujanense por la presencia de Equus (Amerhippus) cf.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sobre la unidad precedente, identifican un nivel litológicamente similar a la Formación La Postrera (sensu Fidalgo et al, 1973a), al que dividen en dos subniveles. El subnivel inferior (Lf M) es el portador de la asociación mamaliana sobre la que establecen la Fauna Local «Centinela del Mar», provisoriamente referida a una nueva Unidad Mamífero denominada «Centinelense», asignable al Pleistoceno Superior y anterior a la Unidad Mamí-fero Lujanense (para una definición de estas unidades bioestratigráficas véase Tonni et al, 1985Tonni et al, , 1987; para una crítica a las mismas véase Cione & Tonni, 1995). El subnivel superior (Lf N) es referido a la Unidad Mamífero Lujanense por la presencia de Equus (Amerhippus) cf.…”
Section: Discussionunclassified
“…Cabe destacar, al menos como antecedente, que E.P. Tonni (apreciación personal en Cione & Tonni, 1995) manifiesta la presencia de fauna ensenadense en los niveles inferiores de CdM.…”
Section: Discussionunclassified
“…In South America, the oldest records of fossil bears are Ensenadan, the 'Puelchan' record could be Ensenadan in age (Cione and Tonni, 1995), and the youngest are latest Lujanian (Early Holocene). According to 14 C dates, the two youngest records in South America are A. tarijense (UMAG 53643, 11,210G50 14 C yr BP, San Roman et al, 2000; GALY s/n, 11,600G130 14 C yr BP, Ubilla and Perea, 1999).…”
Section: Geographic and Stratigraphic Distributionmentioning
confidence: 99%
“…Three specimens (MMMP 162S, 26S, 48S) came from these marine cliffs north of Mar del Plata City. In this area, sediments have been referred to the Ensenadan, Bonaerian, Lujanian, and Platan (Tonni et al, 1992;Cione and Tonni, 1995;1999). Recent magnetostratigraphic studies by Bidegain et al (1998) show that a change from chron C1r to C1n can be identified 7 m above the top of the cliff (3 m from the base).…”
Section: Ensenadanmentioning
confidence: 99%
“…sorgentinii (Cione and Tonni, 1995) known from a partial mandible described in Reig (1957). This fossil is referred to the Vorohuean, a subage of the Marplatan South American Land Mammal Age (Cione and Tonni, 1995). Woodburne et al (2006) correlate the Vorohuean to ~3.0-2.4 MYA.…”
mentioning
confidence: 99%